The Analysis of the Human Development Guide (Education, Health, Income) in the Kurdistan Region for the year 2021: A study in Development Geography (Raparin Journal of Humanities (RJH), 2025)
The aim of this study is to explain the level human development indicators in 2021 Kurdistan Region. The study also tries to conduct research on the current culture of human development indicators in the provinces by studying education, health and income indicators from consumer to producer. Therefore, the current study relied on a descriptive method to analyze the indicators of human development in the Kurdistan Region. Howeve, the stufy relies on scientific analysis, geographical and demographic data in the study area In 2021. After analyzing the indicators of education, health and income, the value of the Human Development Index was (0.680), which is obvious according to the UN report, the Kurdistan Region is in the middle level. Moreover, the life expectancy indicator was (0.83)and the income indicator was (0.415)in the region.